2022
DOI: 10.1371/journal.pone.0261957
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution and associated health risk assessment of urban dust in Riyadh, Saudi Arabia

Abstract: Depending on their particle size and concentration, heavy metals in urban dust pose a health hazard to humans. This study investigated the total concentration, health risk, integrated pollution load index (IPI), and enrichment factor (EF) of various heavy metals in urban dust at different locations in Riyadh City. Surface dust samples were collected from 50 different residential yards in the north, south, west, east, and central corners of the city and analyzed for cadmium (Cd), chromium (Cr), copper (Cu), man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several studies have confirmed that road dust contains contaminants such as polycyclic aromatic hydrocarbons (PAHs), pesticides, and metals [60,61]. In Saudi Arabia, numerous studies have confirmed the presence of heavy metals in road dust matrix, with a positive correlation with proximity to industrial sites that consume or generate trace metals [11,12,62,63]. However, the presence of PFAS in this dust matrix has not been investigated.…”
Section: Road Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that road dust contains contaminants such as polycyclic aromatic hydrocarbons (PAHs), pesticides, and metals [60,61]. In Saudi Arabia, numerous studies have confirmed the presence of heavy metals in road dust matrix, with a positive correlation with proximity to industrial sites that consume or generate trace metals [11,12,62,63]. However, the presence of PFAS in this dust matrix has not been investigated.…”
Section: Road Dustmentioning
confidence: 99%
“…Dust composition, accumulation, and potential consequences may vary due to weather conditions, traffic density, industrial activity, and proximity to mobile soil. There have been only rare studies about the characterization of falling dust in the Arabian Gulf region, mainly focused on reporting the pollutants within urban road dust, particularly trace metals [11][12][13][14][15][16][17][18][19]. While these studies represent a great start to the scientific effort to understand the anthropogenic pollutants mixed with street dust, there is still a need to advance our understanding to include emerging contaminants and study the impact of SDSs on baseline pollution levels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many HMs accumulate in the human body over long periods of time through accidental ingestion, inhalation, and dermal contact, thus causing irreversible damage to human health [ 22 , 23 , 24 ]. Therefore, USD can serve as a comprehensive indicator of the quality of the urban ecological environment [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oasis cities are built on a large-scale desert background substrate, and their urban development is largely constrained by the distribution characteristics of the water system [ 53 , 54 ]. In addition, oasis cities have a dry climate, sparse vegetation, and exposed surfaces due to a low precipitation and high evaporation, and their urban ecological environment is vulnerable to dust storms under the effects of human activities and atmospheric disturbances [ 26 , 55 ]. Luo et al [ 56 ] quantitatively analyzed the contamination and health risk of HMs in the dust of typical oasis cities from sandstorms and found HM contamination derived from anthropogenic activities; moreover, exposure through ingestion poses the greatest health risk to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Road-deposited sediment (RDS) in the urban environment is severely polluted with polycyclic aromatic hydrocarbons (PAHs) and heavy metals worldwide due to traffic and industrial activities (Alghamdi et al, 2022;Al-Shidi et al, 2020;Bisht et al, 2022;Yusuf et al, 2022;Xu et al, 2022). Khpalwak et al (2019) reported that the PAHs concentration in urban road dust was higher than that in aerial dust.…”
mentioning
confidence: 99%